Safety of Levodopa-Carbidopa Intestinal Gel Treatment in Patients with Advanced Parkinson’s Disease Receiving ≥2000 mg Daily Dose of Levodopa - Cindy Zadikoff; Werner Poewe; James T. Boyd; Lars Bergmann; Horia Ijacu; Pavnit Kukreja; Weining Z. Robieson; Janet Benesh; Angelo Antonini (Parkinson's Disease)
Background. Levodopa-carbidopa intestinal gel (LCIG) provides continuous levodopa administration and clinical benefits to patients with advanced Parkinson’s disease (PD). This report evaluates long-term safety and efficacy of high-dose LCIG in PD patients. Methods. Data were collected from several prospective, phase III clinical studies and an observational registry. The phase III program (N = 412) included four multicenter studies: a 12-week, randomized, double-blind study and three open-label studies extending ≥12 months. GLORIA (N = 375) was a 24-month, multicountry, observational registry. LCIG safety (adverse effects (AEs)/adverse drug reactions (ADRs)) and efficacy (modified Unified Parkinson’s Disease Rating Scale (UPDRS) part IV item 32 and 39 scores for “On” time with dyskinesia and “Off” time) were assessed in patients who received ≥2000 mg/day vs <2000 mg/day LCIG. Results. A total of 72 of 412 (17.5%) patients required dosages ≥2000 mg/day LCIG in the phase III program and 47 of 375 (12.5%) patients in GLORIA. Baseline demographics and disease severity were similar between dosage groups with more men in the high-dosage group. Compared with the <2000 mg/day dosage group, patients requiring ≥2000 mg/day LCIG had higher rates of AEs/ADRs including polyneuropathy; improvements in “Off” time and discontinuations due to AEs were similar between dosage groups and lower for discontinuations due to ADRs reported in GLORIA. Conclusions. Patients who require ≥2000 mg/day LCIG exhibited a safety profile comparable to the established safety/tolerability of LCIG with similar clinical improvements. Higher AEs were noted but within what is accepted for LCIG. Continuous administration of LCIG is beneficial to advanced PD patients who require very high doses of levodopa.